POSITIVE DISCOURSE STRUCTURE IN JOKO WIDODO`S SPEECH AT THE BLOOMBERG NEW ECONOMY FORUM IN SINGAPORE - Fitriah, Siti; Putri, Aprilia Kartika; Triandana, Anggi; Putra, Yoga Mestika; Amri, Ulil (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2026)
This study aims to analyze the structure of positive discourse in the speech delivered by Joko Widodo at the Bloomberg New Economy Forum in Singapore. This research employs a qualitative approach using the discourse analysis framework of Teun A. van Dijk, which includes macrostructure, superstructure, and microstructure, combined with the Positive Discourse Analysis approach. The findings reveal that the structure of positive discourse can be identified through macrostructure, superstructure, and microstructure. At the macrostructure level, the speech presents a main theme of Indonesia’s economic transformation toward a data- and technology-based intelligence economy. At the superstructure level, the speech is systematically organized into three main parts—introduction, body, and conclusion—forming a logical and persuasive flow. Meanwhile, at the microstructure level, the analysis covers semantic, syntactic, stylistic, and rhetorical aspects that function to reinforce positive messages such as optimism, progress, and readiness for the future. Therefore, the speech is not only informative but also persuasive and inspirational in constructing a positive image of Indonesia on the global stage.